2022
DOI: 10.1111/os.13413
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Hemorrhage Followed by Vertebral Artery Injury during Cervical Anterior Controllable Antedisplacement and Fusion Surgery: Case Report and Literature Review

Abstract: Background: Vertebral artery injury (VAI) during cervical spine surgery is rare. Anterior controllable ante-displacement and fusion (ACAF) surgery is a novel technique for treating degenerative cervical spine disorders, especially ossification of the posterior longitudinal ligament. To date, there have been no reports of VAI during cervical ACAF surgery. Here, we report a rare case of perioperative complication of VAI during ACAF surgery. The available English literature that provides treatment instructions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In 2021, An TY et al [ 32 ] reviewed the literature on iatrogenic vertebral artery injury and observed increased intraoperative risk during vertebral exposure, decompression, or instrument insertion. Yongjun T and colleagues, in 2022 [ 33 ] reviewing literature regarding late bleeding owing to vertebral artery injury in ACAF technique, underlined that intraoperative local packing with bone graft for bleeding control is the optimum method. They also advocated performing preoperative imaging to discern possible vascular variations and calculate the distance from the transverse foramen and its relationship with the posterior longitudinal ligament.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, An TY et al [ 32 ] reviewed the literature on iatrogenic vertebral artery injury and observed increased intraoperative risk during vertebral exposure, decompression, or instrument insertion. Yongjun T and colleagues, in 2022 [ 33 ] reviewing literature regarding late bleeding owing to vertebral artery injury in ACAF technique, underlined that intraoperative local packing with bone graft for bleeding control is the optimum method. They also advocated performing preoperative imaging to discern possible vascular variations and calculate the distance from the transverse foramen and its relationship with the posterior longitudinal ligament.…”
Section: Resultsmentioning
confidence: 99%
“…[ 26 ] As claimed by Yongjun T et al, who studied the incidence of iatrogenic injury in spinal fusion with the ACAF technique, besides perceiving the anatomical variation of the vessel, the calculation of the distance of the vertebral artery from the transverse foramen and its relationship with the posterior longitudinal ligament is of momentous gravity. [ 33 ] Although literature accentuates the essential requirement for preoperative knowledge of the anatomy and course of the vertebral artery, the imaging technique of choice remains contentious. It is even worth mentioning that according to Tan La et al, preoperative ignorance of vertebral artery anatomy is associated with an upraised incidence of injury at a rate of 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Known risks from the posterior spine approach are due to complex regional vascular neural anatomy and may generate neurological or vascular complications, especially those associated with early or late vertebral artery injury, either of which can be fatal if not quickly recognized. Therefore, it is crucial to prevent this complication and know how to investigate it upon suspicion of vertebral artery (VA) injury [12][13][14][15][16]. Imaging studies play a fundamental role in determining the course of treatment [17].…”
Section: Introductionmentioning
confidence: 99%